ANALISIS PENGUKURAN KINERJA PERUSAHAAN DENGAN KONSEP BALANCED SCORECARD (PT. JASA MARGA TBK. SURABAYA – GEMPOL) - Ida Harahap; Dobson Dobson (Jesya (Jurnal Ekonomi dan Ekonomi Syariah), 2022)
Face environment the business more complex nowday moment to need measurement trada method use can to company measure trade with accurate and entire. The best good method use is Balance Scorecard. The direction use Balance Scorecard measurement for company’s four prespectif. Has four methods as a means of measurement, financial, customer, internal business, and learning and growth. The results of the research reveals that the performance of PT Jasa Marga is good enough, it is indicated by the value generated from the respective scorecards of each perspective Finencial prespectiv deficiency happen on liquidity and activity. Customer prespective: customer acquisition, customer satisfaction, customer retention, customer profitability show thet increase ratios. Internal business prespective is show thet the effectiveness system innovation automatic toll gate. Prespective learning and growth is show thet the reduction level employee retention every year.